Albania : Staff Report for the 2006 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Review Under Extended Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. (IMF Staff Country Reports; Country Report ;, 2006)
Albania's macroeconomic performance over the past year has been good, with strong growth and a significant reduction in poverty under the Poverty Reduction and Growth Facility Arrangement. Executive Directors commended the new strategy for maintaining the macroeconomic stability, enhancement of the budget, and the credibility of the monetary framework. They emphasized the need to accelerate structural reforms, and appreciated the revised strategy for the electricity sector. They stressed the need to improve official statistics to serve as a reliable basis for policymaking and program design.